2014
DOI: 10.1007/s11269-014-0769-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Change of Blue Water and Green Water Resources in the Headwater of Yellow River Basin, China

Abstract: The headwater of Yellow River Basin (HYRB) is crucial for the water resources of the whole basin in Northwest China. Based on the semi-distributed hydrological model "Soil and Water Assessment Tool" (SWAT), the spatiotemporal change trends of blue water and green water resources in the HYRB were analyzed quantificationally. By using the Sequential Uncertainty Fitting program (SUFI-2), the model was calibrated at Tangnaihai hydrological station and uncertainty analysis was performed. The results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…Previous studies of evaluating green water were mainly focused on the green water flow (actual ET) and the green water storage (that is, soil water) [15][16][17][18][19]. To conduct a more comprehensive analysis of the quantity and distribution of green water, three evaluation indices are introduced in this study.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…Previous studies of evaluating green water were mainly focused on the green water flow (actual ET) and the green water storage (that is, soil water) [15][16][17][18][19]. To conduct a more comprehensive analysis of the quantity and distribution of green water, three evaluation indices are introduced in this study.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…The overall hydrologic balance is simulated for each HRU, including: the canopy interception of precipitation, partitioning of precipitation, snowmelt water, redistribution of water within the soil profile, evapotranspiration (ET), lateral subsurface flow from the soil profile, and the return flow from shallow aquifers. SWAT has been widely applied in a range of climatic, topographic, soil, and management conditions around the world to investigate a broad range of hydrological and environmental topics [58], including the cases of snow hydrology studies [59][60][61] and the glacial hydrology studies [38,39,44].…”
Section: Description Of Swatmentioning
confidence: 99%
“…Generally, SWAT allows the sub-watershed to be split into a maximum of ten elevation bands, and the temperature and precipitation for each band to be adjusted using t laps and p laps , respectively. A detailed description has been reported in the model documentation [61]. SWAT2005 is used in this study.…”
Section: Description Of Swatmentioning
confidence: 99%
“…Since then, numerous methods have been used to assess blue water and green water resources. With the development of distributed hydrological models, the temporal-spatial variations of blue and green water resources can be estimated by methods which have a clearer physical mechanism [11,[21][22][23]. It has been demonstrated that the soil and water assessment tool (SWAT) model can simulate blue and green water resources and detect the impacts of climate variability on hydrological components [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%